Guyana : Agricultural Insurance Component Pre-feasibility Study Report - World Bank (Washington, DC, 2013)
The objective of the Agricultural Insurance pre-feasibility study is to identify the institutional, operational, technical and financial challenges for the development of agricultural risk transfer solutions and insurance for rice, fruit and vegetables, livestock, and the aquaculture sector in Guyana. The specific objectives of the study include: (i) to identify the production systems, constraints and risks faced by farmers in Guyana; (ii) to assess the institutional, operational and financial capacity in Guyana to manage an agricultural insurance scheme for the selected activities; (iii) to evaluate the availability of information and collect technical data and information needed for the development of an agricultural insurance scheme for the selected activities; (iv) to assess the potential interest of the possible stakeholders that might get involved in the development of an agricultural insurance scheme in Guyana. This report draws heavily on international experience. International experience on agricultural insurance is vast, as it is currently being implemented in more than 100 countries around the world. This study benefits from this experience, which has been tailored to the local economic and social context of Guyana.